The Effect of Implementing The Teams Games Tournament (TGT) in Improving Learning Interest and Learning Outcomes - Anissa Laily Anissa Septianingtyas; Antin Eka Saputri; Lyan Hanan Shafira; Muhammad Umar Al Maghtani; Nadia Filosofi Dina; Riska Nur Aisya (Assyfa Journal of Islamic Studies, 2024)
This study aims to analyze the effect of implementing the Teams Games Tournament (TGT) cooperative learning method on improving learning interest and learning outcomes of tenth-grade students in Islamic Religious Education (PAI) at Pacitan Development Vocational School. The background of this study is based on the low level of active participation and learning motivation of students in PAI lessons, which impacts on suboptimal academic achievement. The TGT method was chosen because it integrates elements of educational games and group cooperation, thus it is expected to create an interactive, enjoyable, and healthy competitive learning atmosphere. This study uses a quantitative approach with a quasi-experimental design with a pretest-posttest model. The research sample consisted of tenth-grade students selected using a saturated sampling technique. Data collection was carried out through a questionnaire to measure learning interest, a final semester exam (UAS), and observations during the learning process. Data analysis was carried out using a paired sample t-test and multiple linear regression analysis to determine the effectiveness and relationships between variables. The results showed that there was a significant increase in student learning interest and learning outcomes after the implementation of the TGT method. Students became more enthusiastic, active in group discussions, and were able to understand the material more deeply through the games and competitions held. Furthermore, the data showed a positive relationship between learning interest and learning outcomes, indicating that increased learning interest contributes to student academic achievement. Thus, the TGT method has proven effective as a cooperative learning strategy in improving the quality of Islamic Religious Education (PAI) learning at the vocational high school level. This study recommends the continued use of the TGT method by teachers as an innovative effort to create a participatory and meaningful learning environment.